2017
DOI: 10.22159/ijpps.2017v9i10.20249
|View full text |Cite
|
Sign up to set email alerts
|

Anticlastogenicity of Tinospora Cordifolia Stem Extract Against Arsenic Genotoxicity in Mus Musculus Bone Marrow Erythrocytes Using Micronucleus Assay

Abstract: Objective: The study was aimed to evaluate anticlastogenic potential of ethanolic extract of T. cordifolia stem against arsenic induced genotoxicity. Methods:In the experiment twenty five animals were taken and divided into five groups and each group contain five animals. Group 01(control) and fed on tap water while the rest four (02, 03, 04, 05) groups were treated with 4 mg/kg body weight, per orally sodium arsenite for 8 w. Sodium arsenite pretreated groups 04 and 05 were followed by dose of 80 mg/kg body w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…High index of micronucleus frequency was observed in the Groups 2 and 3 in contrast to Group 1 (control) while micronucleus frequency dramatically reduced in 4 and 5 groups. Investigation has shown that the test plant stem extract may have antimutagenic or anticlastogenic property so it is noteworthy in the preventive aspects of chemical carcinogenesis and several types of disorders caused by genetic damages due to arsenic toxicity and T. cordifolia may be used as a preventive herbal drug against chemical or arsenic toxicity [14].…”
Section: Anticlastogenicity Activitymentioning
confidence: 99%
“…High index of micronucleus frequency was observed in the Groups 2 and 3 in contrast to Group 1 (control) while micronucleus frequency dramatically reduced in 4 and 5 groups. Investigation has shown that the test plant stem extract may have antimutagenic or anticlastogenic property so it is noteworthy in the preventive aspects of chemical carcinogenesis and several types of disorders caused by genetic damages due to arsenic toxicity and T. cordifolia may be used as a preventive herbal drug against chemical or arsenic toxicity [14].…”
Section: Anticlastogenicity Activitymentioning
confidence: 99%
“…Thus, the antioxidative potential of GA proves to be substantial against arsenic toxicity. Other studies such as combination therapy, by the utilization of chelating agents and antioxidants, have proven to be effective in toxicity studies [27]. Thus, the combination therapy may serve as a suggested therapeutic for arsenic toxicity, in replacement for the commonly used and less efficient treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous geothermal waters contain high groupings of arsenic. Common arsenic in groundwater at fixations over the drinking water standard of 10 µg/l is not extraordinary [17][18][19][20][21][22][23]. Man-made wellsprings of arsenic, for example, mineral extraction and preparing squander, poultry and swine feed added substances, pesticides, and very solvent arsenic trioxide reserves are additionally normal and have caused the pollution of soils and groundwater.…”
Section: Arsenic In Groundwatermentioning
confidence: 99%